PELAKSANAAN GOLLA KAMBU DALAM MENINGKATKAN PENERBITAN KARTU IDENTITAS ANAK (KIA) DI KABUPATEN MAMUJU PROVINSI SULAWESI BARAT - Saniy Ziyan Fasya Basir; Astri Nur Fauziyah; Elvin Primadhani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The implementation of Child Identity Cards (KIA) in Mamuju Regency experienced delays in implementation which resulted in the issuance and ownership of the card being relatively low and had not reached the national target of 30% even though the Mamuju Regency Population and Civil Registration Office carried out innovative activities in the form of The Population and Civil Registration Ball Movement for Mamuju Regency to improve the quality of population administration services. Purpose: The purpose of this study was to determine the implementation of Golla Kambu in increasing the issuance of Child Identity Cards (KIA), obstacles and efforts to overcome obstacles to the implementation of Golla Kambu in the issuance of Child Identity Cards (KIA). Method: This study uses a descriptive qualitative method with an inductive approach to implementation according to the theory of George R. Terry. Data collection techniques were carried out by interview, observation and documentation. Result: The findings obtained by the authors in this study are that the issuance of Child Identity Cards (KIA) through the implementation of Golla Kambu has increased and is classified as good, although it is still constrained by infrastructure, budget and the level of public awareness and understanding. Conclusion: The implementation of Golla Kambu in increasing the issuance of Child Identity Cards (KIA) has been going well, this is due to the collaboration and coordination of the Population and Civil Registration Office with several local SKPD by utilizing public places and community leaders. In order to optimize the implementation of Golla Kambu, it is recommended to use social media in disseminating information and making standard operating procedures for special procedures for issuing Child Identity Cards (KIA) through Golla Kambu.Keywords: Participation; Youth Generations; Lorong Literasi Gowa Programs